THE INFLUENCE OF COMPETENCE, WORK ENVIRONMENT, AND JOB STRESS ON ORGANIZATIONAL COMMITMENT OF EMPLOYEES IN THE SERVICE OF WOMEN'S EMPOWERMENT CHILD PROTECTION POPULATION CONTROL AND FAMILY PLANNING IN RIAU ISLANDS PROVINCE WITH JOB SATISFACTION AS AN INTE - Syarifah Fatimah; Bambang Satriawan; Nolla Puspita Dewi (CV. RADJA PUBLIKA, 2024)
This study aims to examine the influence of competence, work environment and work stress on organizational commitment of employees of the women's empowerment service, child protection, population control and family planning, Riau Islands province with job satisfaction as an intervening variable. The analysis used in this research is parametric and non-parametric statistics. parametric using SEM-PLS (Structural Equation Modeling-Partial Least Square) The results of this research on direct relationships found that Competence has a negative and insignificant effect on organizational commitment, the work environment has a positive and insignificant effect on organizational commitment, Job stress has a positive and not significant to organizational commitment, Competence has a positive and significant effect on job satisfaction, Work environment has a positive and significant effect on job satisfaction, Job stress has a negative and not significant effect on job satisfaction, Job satisfaction has a positive and significant effect on organizational commitment, in testing the relationship hypothesis It was indirectly found that Competence had a significant positive effect on Organizational Commitment with job satisfaction as an intervening variable, Work environment had a significant positive effect on Organizational Commitment with job satisfaction as an intervening variable, Job stress had a negative and insignificant effect on employee Organizational Commitment with job satisfaction as an intervening variable